Financial well-being among young adult in Klang Valley - Safian, Noorliana; Hussain@ Hamid, Shawal Sahid; Ngah, Nor Syamaliah (2023)
The issue of financial wellbeing is an issue across the globe. According to Malaysian Department of Insolvency, the number of Malaysians that were declared bankrupt is 264,127 up until April 2023. Furthermore, young adults, specifically, according to current Consumer Research and Resource Centre (2012) statistics, have less knowledge and awareness, particularly in terms of personal financial responsibility. Therefore, this study aims to understand the determinants of financial wellbeing among young adults with specific focus in Klang Valley. Three variables were tested against financial wellbeing among young adults, which are financial literacy, financial socialization, and financial behaviour. This study is a quantitative study with 155 respondents involve in this study. The data was analysed using SPSS Version 23. The findings reveal that, all the variables are significantly associated with financial wellbeing among young adults. Future suggestions include implementing financial education in school, financial counselling towards young adult and the utilisation of digital applications for financial managements and improve financial literacy among young adults.